Observation Report on Lack of Early Childhood Cognitive Development (Case Study on Students of Paud Darussalam and Paud Anggrek) - Wulan Nur Hikmah; Siti Nurfaizah; Udi Mufrodi; Ulfah Marhamah; Ulfarizkina (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
Early childhood cognitive development is an important process that occurs from birth to 8 years of age. During this period, children experience very rapid brain development, so they can optimize their cognitive capacity with the help of stimulation and stimulation from the surrounding environment. They begin to understand things, solve problems, and think symbolically, which is characterized by abilities such as recognizing numbers and letters, walking, running, and recognizing colors and shapes. This cognitive development process is very important to form the basis of a child's learning abilities and future success.